2013
DOI: 10.1136/bcr-2012-007754
|View full text |Cite
|
Sign up to set email alerts
|

Brain dead or not? CT angiogram yielding false-negative result on brain death confirmation

Abstract: We describe a case of severe traumatic brain injury with multiple facial and skull fractures where CT angiogram (CTA) failed to yield a definite result of brain death as an ancillary test. A 28-year-old man was admitted following a road traffic accident with a Glasgow Coma Score (GCS) of 3/15 and fixed pupils. CT brain revealed uncal herniation and diffuse cerebral oedema with associated multiple facial and skull fractures. 72 h later, his clinical condition remained the same with high intracranial pressure re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Skull defects or decompressive craniectomy may prevent complete cessation of intracranial blood flow, even when patients otherwise meet clinical criteria for brain death. 70,71 Two systematic reviews have assessed the diagnostic accuracy of CT angiography in the confirmation of brain death. 68,69 Taylor and colleagues identified 10 studies and reported a sensitivity of 84% in relation to the diagnosis of brain death by physical examination and apnea testing.…”
Section: Ct Angiographymentioning
confidence: 99%
“…Skull defects or decompressive craniectomy may prevent complete cessation of intracranial blood flow, even when patients otherwise meet clinical criteria for brain death. 70,71 Two systematic reviews have assessed the diagnostic accuracy of CT angiography in the confirmation of brain death. 68,69 Taylor and colleagues identified 10 studies and reported a sensitivity of 84% in relation to the diagnosis of brain death by physical examination and apnea testing.…”
Section: Ct Angiographymentioning
confidence: 99%
“…19 Os exames complementares comprobatórios mais confiáveis e aceitos de morte encefálica, atualmente, são os que demonstram a total ausência de perfusão sanguínea encefálica, podendo ser demonstrada por angiografia, tomografia computadorizada por emissão de fóton único ou Doppler Transcraniano (DTC). 20 Apesar de poderem ser utilizados outros exames, como por exemplo, os que confirmem a perda da atividade elétrica (eletroencefalografia ou potenciais evocados somatossensoriais) 21 ou atividade metabólica cerebral (PET ou extração cerebral de oxigênio). 8 Neste estudo, o DTC foi utilizado com a mesma frequência que o Eletroencefalograma (EEG).…”
Section: Discussionunclassified
“…However, it has been neglected by others because of controversial results 93,165,170,[182][183][184] .…”
Section: Computed Tomography Angiography (Cta)mentioning
confidence: 99%